2020
DOI: 10.1093/jamia/ocaa156
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth in response to the COVID-19 pandemic: Implications for rural health disparities

Abstract: Telehealth programs have long held promise for addressing rural health disparities perpetuated by inadequate healthcare access. The COVID-19 pandemic and accompanying social distancing measures have hastened the implementation of telehealth programs in hospital systems around the globe. Here, we provide specific examples of telehealth efforts that have been implemented in a large rural healthcare system in response to the pandemic, and further describe how the massive shift to telehealth and reliance on virtua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
225
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(232 citation statements)
references
References 13 publications
7
225
0
Order By: Relevance
“…Combined with lower socioeconomic status and the higher prevalence of overweight and obesity in rural areas, attention to rural communities is important (Lakhani et al 2020). In addition, many rural areas in the US are poorly prepared to manage the pandemic, and innovative responses such as telehealth have not yet been widespread enough to combat these problems (Lakhani et al 2020;Hirko et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Combined with lower socioeconomic status and the higher prevalence of overweight and obesity in rural areas, attention to rural communities is important (Lakhani et al 2020). In addition, many rural areas in the US are poorly prepared to manage the pandemic, and innovative responses such as telehealth have not yet been widespread enough to combat these problems (Lakhani et al 2020;Hirko et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This prompts health care seeking (ability to seek), followed by actually getting (ability to reach) and utilising health care, which is affected by patients’ ability to pay and ability to engage, which will lead to improvements in health, provided the health care is effective. Research pre-COVID-19 showed that telehealth can improve access to health care for those in rural areas or with restricted ability to travel but those with poor internet connections (which, perversely, may be worse in rural areas), English as a second language or privacy concerns may be disadvantaged [ 11 , 12 ]. Equitable access is foundational to good primary care [ 10 , 13 ] and relates not only to patient characteristics but also to the quality and availability of services.…”
Section: Introductionmentioning
confidence: 99%
“…Rural regions tend to have higher levels of poverty (8), fewer job opportunities (9), and heightened vulnerability to labor market shocks (10) relative to urban areas. Further, they broadly lack access to healthcare (11), now see a heightened reliance on telehealth (12), tend to have older and health-compromised populations (13,14), face serious barriers to enrollment in clinical trials (15), and have far more limited access to COVID-19 testing (16).…”
mentioning
confidence: 99%